2000
DOI: 10.1111/j.1572-0241.2000.02263.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of nonsteroidal antiinflammatory drugs in patients with inflammatory bowel disease

Abstract: Among this group of outpatients, NSAID use was not associated with a higher likelihood of active IBD. NSAID use in IBD deserves further study before recommending that patients refrain from their use under all circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 11 publications
1
40
1
Order By: Relevance
“…Smale et al (14) reported that 25% of IBD patients treated for 1 month with naproxen or nabumetone had clinical relapse. A series of retrospective studies has found no association between the use of NSAIDs and IBD relapse (15,16). Bonner and Vennamaneni (17) completed a prospective cohort study to examine the use of NSAIDs (including over-the-counter medications) and disease activity in 368 patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Smale et al (14) reported that 25% of IBD patients treated for 1 month with naproxen or nabumetone had clinical relapse. A series of retrospective studies has found no association between the use of NSAIDs and IBD relapse (15,16). Bonner and Vennamaneni (17) completed a prospective cohort study to examine the use of NSAIDs (including over-the-counter medications) and disease activity in 368 patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported in 2000 comprising outpatients with IBD (both Crohn's disease and ulcerative colitis) compared the frequency of NSAID usage in patients whose disease flared with that of patients whose IBD remained quiescent [30]. The investigators found no significant differences in the frequency of NSAID usage between those two groups.…”
Section: Nsaid Use In Ibd: Do Clinical Studies Provide the Evidence Fmentioning
confidence: 95%
“…They found that only 7.4 percent of patients who used COX-2 inhibitors for a median duration of nine months had aggravation of their IBD. 69 Similarly, Bonner et al 70 found that there was no significant difference in exacerbation of IBD among 368 patients with IBD who were not taking NSAIDS, low-dose NSAIDs, or high-dose NSAIDs.…”
Section: Nsaids and Ibdmentioning
confidence: 96%
“…68 In contrast, some studies have found no link between NSAID use and exacerbation of IBD. [69][70][71] Karmeli et al 72 found that COX-2 inhibitors have a beneficial effect on experimental colitis in rats, via reducing colonic eicosanoids generation. 72 However, Lesch et al 73 showed that COX-2 inhibitors have no beneficial effect in experimental colitis.…”
Section: Nsaids and Ibdmentioning
confidence: 98%
See 1 more Smart Citation